(4y+9)(2+y)=0

Simple and best practice solution for (4y+9)(2+y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4y+9)(2+y)=0 equation:


Simplifying
(4y + 9)(2 + y) = 0

Reorder the terms:
(9 + 4y)(2 + y) = 0

Multiply (9 + 4y) * (2 + y)
(9(2 + y) + 4y * (2 + y)) = 0
((2 * 9 + y * 9) + 4y * (2 + y)) = 0
((18 + 9y) + 4y * (2 + y)) = 0
(18 + 9y + (2 * 4y + y * 4y)) = 0
(18 + 9y + (8y + 4y2)) = 0

Combine like terms: 9y + 8y = 17y
(18 + 17y + 4y2) = 0

Solving
18 + 17y + 4y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(9 + 4y)(2 + y) = 0

Subproblem 1

Set the factor '(9 + 4y)' equal to zero and attempt to solve: Simplifying 9 + 4y = 0 Solving 9 + 4y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 4y = 0 + -9 4y = 0 + -9 Combine like terms: 0 + -9 = -9 4y = -9 Divide each side by '4'. y = -2.25 Simplifying y = -2.25

Subproblem 2

Set the factor '(2 + y)' equal to zero and attempt to solve: Simplifying 2 + y = 0 Solving 2 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Simplifying y = -2

Solution

y = {-2.25, -2}

See similar equations:

| -(8x-8y-5)= | | 6x+20y=16 | | 6x^2+10x-9=0 | | (X-4)2+5=30 | | 5t-3=3t+10 | | 20x+2x=40000 | | 14x-8x^2=0 | | 9(2y-3)-(6y+7)= | | -3z(4z^2-4)=0 | | 20x-1=37x+1 | | -(3s+4t)+(-s-4t)= | | 6x-15=7x-20 | | 3x+8=-7x+6 | | z^2-6x+9=0 | | n=70+y | | 57+10x=111-2x | | 6s-16=80 | | 5x+5=4x+11 | | 60=3107n | | 7.5/.8 | | 7+4x=4+x | | -28n+14n+33=-23 | | X+14=3x+18 | | kx^2-(3k+2)x+7=0 | | Z+10=0 | | 18y-2+10x=180 | | (5x-12)(5x-1)= | | z+10=10 | | 5x+1=11x-6 | | 9x-20-x^2=0 | | 13x^2+12x+2=0 | | 4(2-3)=52 |

Equations solver categories